Effects of A‐Site Sm Substitution and Textured Structure on Electric Properties of CaBi2Nb2O9‐Based High‐Curie‐Temperature Ceramics. (8th April 2013) - Chen, Huanbei; Guo, Xiangxin; Cui, Zhonghui; Zhai, Jiwei
Abstract : CaBi2 Nb2 O9 ceramic is a promising candidate for high‐temperature piezoelectric applications due to its high Curie temperature. However, extremely low piezoelectric properties hinder its application. A combination of Sm 3+ donor doping and texturing was applied to address this problem. Piezoelectric coefficient, T c, and resistivity of textured Ca0.95 Sm0.05 Bi2 Nb2 O9 ceramics ( d 33 = 23pC/N, T c = 941°C, ρ = 4.1 × 10 5 Ω cm at 600°C) were obviously higher than those of pure random CaBi2 Nb2 O9 ceramics ( d 33 = 6, T c = 930°C, ρ =0.6 × 10 5 Ω cm at 600°C). Furthermore, it had excellent resistance to depolarization property, with k p of about 5.9% until 600°C.